Analisis Faktor Yang Mepengaruhi Penggunaan Transportasi Laut Pada Pt. Dharma Lautan Utama Cabang Sampit - Hendrik Sugiharto; Dedy Rusmiyanto (Jurnal Sains dan Teknologi, 2023)
Transport by sea is a commercial shipping business that operates in the field of providing sea cargo transportation services where the business activities are very broad in scope and play an important role in advancing domestic and foreign trade, including in efforts to facilitate the flow of goods from production areas to consumer areas. This research aims to to determine the influence of price, service quality and promotion on the interest of users of sea transportation services. The population in this study were passengers on the Dharma Lautan Utama ship and the sample used in this study was 100 respondents. The sampling technique used was simple random sampling probability sampling, then the data was analyzed using multiple linear regression with the help of (software) Statistical Package For Social Science (SPSS) Version 26. The regression formulation in this research is as follows: Y = 0.733 + 0.333X1 + 0.203X2 + 0.385X3 + µ From this equation it is known that the most dominant variable influencing the interest of users of sea transportation services is the promotion variable with a regression coefficient of 0.385. The R2 (R Square) test obtained a result of 0.561 or 56.1%, which means that the interest of sea transportation service users (Y) can be explained by independent variables, namely price (X1), service quality (X2) and promotion (X3). ). Meanwhile, the remainder (100%-61.9% = 38.1%) is explained by other variables outside the model which are not explained in this research.